The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/jth.13482
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte oxidative stress is associated with cell deformability in patients with retinal vein occlusion

Abstract: Essentials• Retinal vein occlusion (RVO), characterized by blood hyperviscosity, has an unclear pathogenesis.• We aimed to find out if hemorheological profile is altered by oxidative stress in RVO patients.• Red blood cell (RBC) oxidative stress is associated to whole blood viscosity and RBC deformability.• Reactive oxygen species alter RBC membrane rigidity, playing a key role in RVO pathogenesis.Summary. Background: Retinal vein occlusion (RVO) is characterized by vision loss resulting from hypoperfusion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 59 publications
1
40
0
2
Order By: Relevance
“…This review will briefly summarize what is currently known about the involvement of RBCs in hemostasis and thrombosis and its underappreciated importance. RBCs increase blood viscosity because of a rise in hematocrit, an increase in RBC aggregation or a decrease in RBC deformability (increasing flow resistance) Pro [2][3][4][5] Conversely, anemia is associated with low blood viscosity and bleeding tendency as a result of reduced platelet margination toward endothelium and enhanced NO availability Anti [2][3][4][5] RBCs undergo shear-dependent reversible aggregation mediated by plasma proteins (mainly fibrinogen and immunoglobulins) and/or local osmotic gradient Pro [14][15][16][70][71][72][73][74] RBCs with increased rigidity occlude small vessels Pro [11,12] Deformability of RBCs reduces frictional resistance to flow Anti [8,[11][12][13]] RBCs maintain biconcave shape and a high surface-to-volume ratio as a result of cytoskeleton and water/ions balance Pro or anti [5] RBCs migrate to the center of blood flow and push platelets toward the endothelium (margination) in a hematocrit-and shear-dependent manner Pro [59][60][61] Effects on platelet reactivity RBCs increase platelet adhesion and aggregation by release of ADP and thromboxane A 2 Pro [66,67] RBCs form aggregates with platelets via adhesive molecules (ICAM-4 and fibrinogen with aIIbb3)…”
Section: Introductionmentioning
confidence: 99%
“…This review will briefly summarize what is currently known about the involvement of RBCs in hemostasis and thrombosis and its underappreciated importance. RBCs increase blood viscosity because of a rise in hematocrit, an increase in RBC aggregation or a decrease in RBC deformability (increasing flow resistance) Pro [2][3][4][5] Conversely, anemia is associated with low blood viscosity and bleeding tendency as a result of reduced platelet margination toward endothelium and enhanced NO availability Anti [2][3][4][5] RBCs undergo shear-dependent reversible aggregation mediated by plasma proteins (mainly fibrinogen and immunoglobulins) and/or local osmotic gradient Pro [14][15][16][70][71][72][73][74] RBCs with increased rigidity occlude small vessels Pro [11,12] Deformability of RBCs reduces frictional resistance to flow Anti [8,[11][12][13]] RBCs maintain biconcave shape and a high surface-to-volume ratio as a result of cytoskeleton and water/ions balance Pro or anti [5] RBCs migrate to the center of blood flow and push platelets toward the endothelium (margination) in a hematocrit-and shear-dependent manner Pro [59][60][61] Effects on platelet reactivity RBCs increase platelet adhesion and aggregation by release of ADP and thromboxane A 2 Pro [66,67] RBCs form aggregates with platelets via adhesive molecules (ICAM-4 and fibrinogen with aIIbb3)…”
Section: Introductionmentioning
confidence: 99%
“…Cell viability, controlled by flow cytometry with propidium iodide staining, was found to exceed 95%. The erythrocyte ROS production was analysed as previously reported [16]. For a single analysis, the fluorescence signals of 100,000 erythrocytes were collected.…”
mentioning
confidence: 99%
“…Thirty studies were conducted in specific anatomic categories of surgery. The two largest surgical categories were urologic (13) and abdominal (9). The urologic series had the highest number of positive studies for transfusion and thrombosis, with three MV-positive correlations and three UV-only positive correlations (no MV done), plus Yoo et al 48 who found a positive RBC volume correlation.…”
Section: Resultsmentioning
confidence: 96%